Natural Orifice-Assisted Laparoscopic Appendectomy - Nezhat, Ceana (Society of Laparoendoscopic Surgeons, 2009)
BACKGROUND AND OBJECTIVES: Natural orifice transluminal endoscopic surgery involves the introduction of instruments through a natural orifice into the peritoneal cavity to perform diagnostic and therapeutic surgical interventions. We report the utilization of the vaginal opening at the time of laparoscopic-assisted vaginal hysterectomy or total laparoscopic hysterectomy as a natural orifice for appendectomy. METHODS: We reviewed cases of 42 patients who underwent total laparoscopic hysterectomy or laparoscopic-assisted vaginal hysterectomy followed by appendectomy, performed by applying a stapler and removing the appendix transvaginally. By using a small-diameter laparoscope, the appendix was mobilized, especially in patients with adhesions, endometriosis, or retrocecal appendix, to facilitate transvaginal access with the stapler. RESULTS: All procedures were performed successfully without intraoperative or major postoperative complications. The appendectomy portion of the procedure took approximately 5 minutes to 10 minutes. Appendiceal pathology included serosal adhesions (14), fibrous obliteration of the lumen (12), endometriosis (4), serositis (2), and carcinoid tumor (1), among others. CONCLUSIONS: Appendectomy performed with an endoscopic stapler introduced transvaginally for amputation and retrieval following total laparoscopic hysterectomy or laparoscopically assisted vaginal hysterectomy appears to be a safe and effective modification of established techniques with acceptable outcomes.